Wege der Kooperation im Kontext inklusiver Bildung - Serke, Björn; Streese, Bettina (Verlag Julius Klinkhardt, 2022)
To cope with increasing school inclusion processes, (multi-)professional cooperation in inclusive schools is considered a central factor. Current studies show that school cooperation needs to be further developed and professionalized. This anthology addresses current issues regarding multi-professional cooperation as well as professionalization for cooperation in the context of inclusive education. Theoretical concepts, empirical findings, practical insights as well as professionalization possibilities for school actors are presented.